2010
DOI: 10.1177/0146621609355279
|View full text |Cite
|
Sign up to set email alerts
|

MIMIC Methods for Assessing Differential Item Functioning in Polytomous Items

Abstract: Three multiple indicators-multiple causes (MIMIC) methods, namely, the standard MIMIC method (M-ST), the MIMIC method with scale purification (M-SP), and the MIMIC method with a pure anchor (M-PA), were developed to assess differential item functioning (DIF) in polytomous items. In a series of simulations, it appeared that all three methods yielded a wellcontrolled Type I error rate when tests did not contain any DIF items. M-ST and M-SP began to yield an inflated Type I error rate and a deflated power when te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 28 publications
1
60
0
1
Order By: Relevance
“…Chen & Anthony, 2003;Christensen et al, 1999;Finch, 2005;Fleishman, Spector, & Altman, 2002;Gelin, 2005;Grayson, Mackinnon, Jorm, Creasey, & Broe, 2000;Hagtvet & Sipos, 2004;MacIntosh & Hashim, 2003;Mast & Lichtenberg, 2000; O. Muthén, Kao, & Burstein, 1991;Oishi, 2006;Schroeder & Moolchan, 2007;Shih & Wang, 2009;Wang & Shih, 2010). Thus, Figure 6 depicts only uniform DIF in the MIMIC-DIF model.…”
Section: Figure 5 Mimic Modelmentioning
confidence: 99%
“…Chen & Anthony, 2003;Christensen et al, 1999;Finch, 2005;Fleishman, Spector, & Altman, 2002;Gelin, 2005;Grayson, Mackinnon, Jorm, Creasey, & Broe, 2000;Hagtvet & Sipos, 2004;MacIntosh & Hashim, 2003;Mast & Lichtenberg, 2000; O. Muthén, Kao, & Burstein, 1991;Oishi, 2006;Schroeder & Moolchan, 2007;Shih & Wang, 2009;Wang & Shih, 2010). Thus, Figure 6 depicts only uniform DIF in the MIMIC-DIF model.…”
Section: Figure 5 Mimic Modelmentioning
confidence: 99%
“…But as demonstrated in Wang and Shih [25], there is also evidence about the effectiveness of the iterative purification method. For the permutation method we used for the detection of anchor items, it is known to be sometimes conservative [37], thus it will take more extreme test statistics to reject a null hypothesis and the actual error rate is much less than the prescribed alpha level.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of anchor items detection has been previously discussed [25] and is not trivial when there is a large amount of DIF in the items of interest. Zenisky, Hambleton and Robin [26] found that when at least 30% of items have DIF, lack of identification of anchor items can result in a substantial change in items that are detected as having DIF.…”
Section: Methodsmentioning
confidence: 99%
“…Since the large sample made most DIF contrasts statistically significant, we chose a clinically significant DIF contrast that was based on ≥ .7 logit difference for all comparisons which is approximately half of a standard deviation (SD = 1.35) for the persons. Standards for what is considered an important DIF effect size vary from about .4 to .6 logits (see Longford, Holland, Thayer; 1993; Paek, 2002; Draba, 1977; Elder, McNamara, & Congdon, 2003; Scheunemann & Subhiyah, 1998; Wang, 2000). In this paper, we used the criterion of .7 logit or larger since we believed that most would agree that this is a large, important DIF contrast, and half a standard deviation is a common criterion for clinical significance (Cohen, 1988; Norman, Sloan, & Wyrwich, 2003; Wolf, 1986).…”
Section: Methodsmentioning
confidence: 99%